Shakespeare, national poet-playwright - Cheney, Patrick Gerard (Cambridge University Press, 2004)
Reassessing Shakespeare as a poet and dramatist, Patrick Cheney contests critical preoccupation with Shakespeare as "a man of the theatre" by reclaiming his original standing as an early modern author. Cheney considers him as a working dramatist who composed extraordinary poems and traces Shakespeare's literary origins to his favorite author, Ovid. Although the book concentrates on Shakespeare's poems, it makes frequent reference to the plays, and ranges widely through the work of other Renaissance writers